A proximal retarding field analyzer for scanning probe energy loss spectroscopy - Richard Palmer (Nanotechnology, 2017)
NanotechnologyPAPER • THE FOLLOWING ARTICLE IS OPEN ACCESSA proximal retarding field analyzer for scanning probe energy loss spectroscopyKarl Bauer, Shane Murphy and Richard E PalmerPublished 8 February 2017 • © 2017 IOP Publishing LtdNanotechnology, Volume 28, Number 10Download Article PDFFiguresReferencesDownload PDF1206 Total downloads 11 citation on Dimensions.Article has an altmetric score of 1Turn on MathJaxShare this articleShare this content via emailShare on FacebookShare on TwitterShare on Google+Share on CiteULikeShare on MendeleyHide article informationAuthor e-mailsr.e.palmer@bham.ac.ukAuthor affiliationsNanoscale Physics, Chemistry and Engineering Research Laboratory, School of Physics and Astronomy, University of Birmingham, Edgbaston, Birmingham, B15 2TT, United KingdomORCID iDsKarl Bauer https://orcid.org/0000-0003-0664-2082DatesReceived 10 October 2016Accepted 13 January 2017Accepted Manuscript online 13 January 2017Published 8 February 2017 Check for updates using CrossmarkPeer review informationMethod: Single-blindRevisions: 1Screened for originality? YesCitationKarl Bauer et al 2017 Nanotechnology 28 105711Create citation alertDOIhttps://doi.org/10.1088/1361-6528/aa5938Buy this article in print Journal RSS feed Sign up for new issue notificationsAbstractA compact proximal retarding field analyzer for scanning probe energy loss spectroscopy measurements is described. Using the scanning tunneling microscope (STM) tip as a field emission (FE) electron source in conjunction with this analyzer, which is placed at a glancing angle to the surface plane, FE sample current and electron reflectivity imaging may be performed simultaneously. This is demonstrated in measurements of Ag nanostructures prepared on graphite by electron-beam lithography, where a material contrast of 13% is observed, with a lateral resolution of 25 nm, between the silver and graphite in electron reflectivity images. Topological contrast mechanisms such as edge enhancement and shadowing are also observed, giving rise to additional features in the electron reflectivity images. The same instrument configuration has been used to measure electron energy loss spectra on bare graphite, where the zero loss peak, π band plasmon loss peak and secondary electron peaks are observed. Using this simple and compact analyzer an STM, with sufficient open access to the tip-sample junction, may easily be augmented to provide simultaneous elemental and topographic mapping, supplementing STM image measurements with FE sample current and electron reflectivity images, as well as electron energy loss spectroscopy measurements, in the same instrument.